Developmental Validation of the Novel Five-Dye-Labeled Multiplex Autosomal STR Panel and Its Forensic Efficiency Evaluation - Huang, Shimei; Jin, Xiaoye; Zhang, Hongling; Jin, Haiying; Ren, Zheng; Wang, Qiyan; Liu, Yubo; Ji, Jingyan; Yang, Meiqing; Zhang, Han; Zheng, Xingkai; Song, Danlu; et al. (Frontiers in Genetics, 2022)
Short tandem repeats (STRs) are the most frequent used genetic markers in forensic genetics due to their high genetic diversities and abundant distributions in the human genome. Currently, the combined DNA index system is commonly incorporated into various commercial kits for forensic research. Some novel STRs that are different from the combined DNA index system not only were used to assess complex paternity cases, they also could provide more genetic information and higher forensic efficiency in combination with those commonly used STRs. In this study, we validated forensic performance of a novel multiplex amplification STR panel to evaluate its sensitivity, species specificity, forensic application values and so on. Obtained results revealed that the kit showed high sensitivity, and all loci could be observed at 0.125pg DNA sample. Besides, the kit possessed high species specificity, good tolerance to common inhibitors, and accurate genotyping ability. More importantly, STRs out of the kit displayed high discrimination power and probability of exclusion. To sum up, the novel kit presented in this study can be viewed as a promising tool for forensic human identification and complex paternity analysis.